Nepal-India Cross Country Tourists’ Mobility: Socio-Economic Impact - Kharel, Suman; Kharel, Khom Raj; Upadhyaya, Yadav Mani (Nepalese Journal of Development and Rural Studies, 2022)
This study analyzes the economic impact of the mutual tourism relationship between Nepal and India on the economies of both the countries. The main objective of this study is to study the exchange earning due to mutual tourism of both the countries and its effect on the economic development. Its method of study is to fit simple regression models for to analyze the trend of tourism of both the countries by using the use secondary data for this applying descriptive and analytical research design. In the discussion of this study, it is said that mutual tourism in Nepal and India as well as in the world community has helped to raise the country’s foreign exchange earnings. Also, this study concludes that there is a positive relationship between tourist arrival and exchange earning. From this, tourism has made a great contribution to the economic development of both the countries. This is further confirmed by economic model R2 and P-value. The study demands more attention should paid for the development of tourism economy in both countries and tourism and travel facilities should improve to excess of tourism economy in Nepal and India.